UNVEILING AND GENERATING AWARENESS ABOUT AUTISM IN PUNE DISTRICT IN INDIA: AUTISM AWARENESS (Proceedings of the World Disability & Rehabilitation Conference, 2025)
Autism Spectrum Disorder (ASD) It is a developmental disorder that impairs the ability to communicate and interact. Children and adults on the spectrum find difficulty in communication, play, understanding emotions, unfamiliar situations and change in routine. The prevalence of autism has been increasing over the past few years. 1 in 68 children in India are autistic. As per World Health Organization, Care for autistics needs to be accompanied by actions at community and societal levels for greater accessibility, inclusivity and support. Scientifically backed sustained early interventions can have a positive impact on the quality of life of the individual and their families. A general public awareness in an urban setup in Pune was assessed and information about autism was shared in direct interviews and awareness sessions. The survey included testing the general awareness, signs and symptoms, knowledge about care and inclusion, reducing stigma and debunking common myths about autism and understanding if their school or office environment was inclusive for autism. Coefficient of Autism Awareness was calculated, it revealed that the awareness does not have any statistical correlation with age, education, income, profession. Awareness should be targeted at all levels of society, regardless of demographic factors. This inclusive approach is essential to ensure that information about autism reaches individuals across diverse backgrounds and demographics. Inclusive Education is deemed to be best foot forward for sustainability. However, the diverse individual needs of the population have to be understood in depth. Autism being one of key diversities impacting education of many, needs more awareness from policy makers to implementers.
Keywords: Autism Spectrum Disorder (ASD); Autism awareness; disability inclusion; Coefficient of Autism Awareness (CoA); inclusive education; awareness survey